2013
DOI: 10.1007/978-94-007-7454-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Introduction and Augmentation of Parasites in and on Domesticated Livestock

Abstract: Parasites are one of the most important threats to domesticated livestock worldwide. For several decades, their control has been based only on therapeutic interventions using chemical products at fixed intervals throughout the year. Results have demonstrated that dependence on these chemical products, as a single form of control, is not economically and ecologically sustainable. The problem has been augmented due to the emergence of endoparasite and ectoparasite populations resistant and multiresistant to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…Therefore, the long-term coevolution between herbivores and PSC necessarily entails the triggering of adaptive responses, which correspond mainly to behavioral and physiological mechanisms that involve both pre-ingestive and post-ingestive processes. Those same mechanisms were used to their full extent when domestic ruminants were introduced to the American continent or to islands such as Australia in more recent years, forcing animals to implement different adaptation mechanisms that have only evolved within the last 500 years [ 6 ]. We encourage readers to consult reviews in this subject in order to gain a complete perspective of the mechanisms by which ruminants cope with PSC [ 18 , 21 , 56 ].…”
Section: Unravelling the Heterogeneous Context Of The Low Deciduoumentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the long-term coevolution between herbivores and PSC necessarily entails the triggering of adaptive responses, which correspond mainly to behavioral and physiological mechanisms that involve both pre-ingestive and post-ingestive processes. Those same mechanisms were used to their full extent when domestic ruminants were introduced to the American continent or to islands such as Australia in more recent years, forcing animals to implement different adaptation mechanisms that have only evolved within the last 500 years [ 6 ]. We encourage readers to consult reviews in this subject in order to gain a complete perspective of the mechanisms by which ruminants cope with PSC [ 18 , 21 , 56 ].…”
Section: Unravelling the Heterogeneous Context Of The Low Deciduoumentioning
confidence: 99%
“…When domestic ruminants were introduced to the LDF, they also brought their own internal and external parasites. Those parasites also had to become adapted to the new conditions to which they were exposed, particularly the free-living phases that must survive outside the host [ 6 ]. The level of success in the survival of parasites in different environmental conditions is the main cause of differences in the array of parasite species present in each region of the world.…”
Section: Unravelling the Heterogeneous Context Of The Low Deciduoumentioning
confidence: 99%
See 1 more Smart Citation
“…Results have shown that dependence on these chemical products, as the only form of control, is neither economically nor ecologically sustainable. Sustainable cattle production needs strong changes, such as considering both agroecology-oriented and novel tick-control approaches (Alonso-Díaz et al, 2014 ). This latter has motivated the exploration of alternative methods for tick control (Samish et al, 2004 ), such as the use of entomopathogenic fungi (EPF).…”
Section: Introductionmentioning
confidence: 99%
“…When ectoparasiticides are administered correctly (dosed and targeted), they are effective and have wide safety margins for both the animals and the people who apply them. However, there are factors such as resistant or multiresistant parasites and/or incorrect ways of applying the medications, which decrease their effectiveness (Alonso-Díaz et al, 2014 ). Currently, global results reveal that parasite control schemes based on a rigorous and exclusive use of chemical applications are not sustainable.…”
Section: Introductionmentioning
confidence: 99%